The Influence of the Science Technology Engineering and Mathematics Approach with Mind Maps on the Higher Order Thinking Skills (HOTS) of Students in Biology Learning Class X SMA N 4 Kerinci - Abdul Razak; Tomi Apra Santosa; Lufri Lufri; Irdawati Irdawati (International Journal of Education and Literature, 2024)
This study aims to determine the effect of the mindmap-assisted STEM approach on students' Higher Order Thinking Skills in learning biology class X SMA Negeri 4 Kerinci. This research is experimental research with a group pretest-posttest design model. The population in this study came from students of class X MIPA SMA Negeri 4 Kerinci in the academic year 2021/2022. The research sample was students of class X MIPA 2 and Class X MIPA 4. The sampling technique used was the random sampling technique. The data collection technique in this study was in the form of an objective test consisting of 20 HOTS questions that had been validated by experts. Data analysis is quantitative data analysis with tests using the SPSS 21 application. The results of the study can be concluded that the STEM approach has a significant effect on students' higher-order thinking skills in learning biology with the results of hypothesis testing 0.00 < 0.05. Furthermore, the STEM approach can increase students' HOTS in biology learning, the average score of the experimental class students is 85.76 and the control class is 70.31.